Shared Decision-Making and Role Preference Among Patients With Schizophrenia in Malaysia: A Cross-Sectional Study - Ismail, Mohamad Ayob; Midin, Marhani (Frontiers in Psychiatry, 2021)
Introduction Shared decision-making (SDM) is recognized as a promising strategy for improving collaboration between clinicians and their patients in achieving recovery. In Malaysia, SDM among people with schizophrenia is still lacking both in practice and research. This study aimed to determine the level of SDM and role preference, and their associated factors, among patients with schizophrenia in Malaysia. Methods A cross-sectional study was conducted on 86 outpatient attendees with schizophrenia at a teaching hospital in Kuala Lumpur, Malaysia. The Nine-Item Shared Decision Making Questionnaire and Control Preference Scale were used to assess perceived SDM experience and role preference, respectively. Linear and logistic regression models were used to analyze the factors associated with SDM and role preference, respectively. Factors with a p-value of <0.25 from the simple regression analyses were controlled as the covariates in the multiple regression analyses. Results The study respondents were predominantly female, single, and unemployed, with a mean age of 44. Only 35% of the participants reported having high SDM experiences, even though the majority (56%) preferred autonomous role preference. Among the participants who preferred autonomous roles, only 40% experienced high SDM. High SDM was found to be significantly associated with being younger (B=-0.33, 95%CI=-0.67- -0.003) and being non-clozapine users (B=19.90, 95%CI=9.39-30.41), while, autonomous role preference was significantly associated with a lower level of insight (Adjusted Odd Ratio (AOR)=0.84, 95%CI=0.72-0.99) and being on oral antipsychotic drugs only (AOR=2.94, 95%CI=1.10-7.82). Conclusion The practice of SDM is still lacking in the treatment of patients with schizophrenia in Malaysia, even though many of them preferred to be involved in the decision-making pertaining to their treatment. This study indicates the need for clinicians to improve their patients’ involvement in the treatment process. More research is needed on how SDM can be implemented with patients with schizophrenia, especially in Asian population settings.